Effects of annealing on the temperature coefficient of resistance of nickel film deposited on polyimide substrate. (February 2019) - Sun, Baoyun; Wang, Pengbin; Ma, Binghe; Deng, Jinjun; Luo, Jian
Abstract: This study investigates the effects of annealing temperature as well as time on the temperature coefficient of resistance (TCR) of nickel (Ni) films deposited on flexible polyimide substrate by direct current magnetron sputtering. The morphological and microstructural characteristics of as-deposited and annealed Ni films were analyzed to understand the mechanisms of TCR variation. The crystalline phase, grain size change tendency and residual stress of films were evaluated by X-ray Diffractometer (XRD) technique. (111) is the preferred orientation of Ni and the grains have a growth after annealing. The residual stress in as-deposited films is about −446.3 MPa and reduced to −208.8 MPa after annealing at 400 °C for 6 h. Focused Ion Beam Electron Microscope (FIBEM) and Energy Dispersive X-ray Spectroscopy (EDS) investigations showed the microstructure of annealed films has a relative improvement and the oxygen content was little increased with increasing annealing temperature and time. Mean surface roughness determined by Atomic Force Microscope (AFM) is decreased from 4.5 nm to 1.25 nm with increasing annealing temperature. The TCR value increases with the increasing annealing temperature and time. When the annealing time exceeds 6 h, the TCR almost has no change or even begin to decline. Highlights: Annealing treatment resulted in larger grain size, residual stress relaxation and smaller surface roughness of Ni films. The TCR shows a significant increase with the increasing annealing temperature below 400℃ and time below 6 h. The TCR shows saturated value after 6 h annealing indicated the Ni films reach stable state within 6 h.